The humanism in Shakespeare’s work: The humanism in Shakespeare’s work - Karimov, Davron (Maktabgacha taʼlim jurnali, 2021)
Humanists were understood as somebody in possession of love for humankind, also as someone who learned humane arts to achieve assumptive level of knowledge, writing or speaking eloquence and, of course, the understanding of the world and history.We can see humanistic ideals in Shakespeare’s plays for instance Hamlet and Julius Ceaser. W.Shakespeare demonstrated the ideas of Renaissance humanism, even his tragic plays and he also presented characters lively the principles and ideals of Renaissance humanism. Shakespeare was an artist who could understand deeply the humanity and an uncanny ability for self-expression who openly practiced and celebrated the ideals of intellectual freedom. It is clear that, Shakespeare did not study like other dramatists who lived at that period. In spite of this, his knowledge is regarded as the grounded in humanism.